Risk factors for the persistence of respiratory symptoms in childhood asthma - (:unkn) unknown (ELSEVIER SCIENCE INC, 2001)
Objective: To evaluate the parameters which could predict the persistence of respiratory symptoms in asthmatic children who have been treated with a considerably uniform therapy. Methods: A retrospective review was performed on the records of 279 children with asthma. An end of study visit, results of spirometry and prick tests completed the data. The mean age at referral and at final visit was 6.2 +/- 3.7 years and 8.9 +/- 4.1 years, respectively; and the children were followed up for a mean of 3 +/- 1.2 years. Results: Eighty-five of the 279 patients (30%) experienced no respiratory symptoms in the previous 12 months. There was no significant difference between those with and without current respiratory symptoms with respect to age, sex, age at onset of symptoms, duration of followup, age at referral, therapeutic choice, severity of asthma and duration of symptoms at referral. For subjects with current respiratory symptoms the initial serum total IgE level, and the percentage of RAST/prick test positivity was significantly higher than those without current respiratory symptoms (P = 0.0027, P = 0.011, respectively). Although the initial FEF25%-75%, FEV1, and FEV1/FVC was significantly lower in those with current respiratory symptoms (P 0.003; P = 0.005; and P = 0.04, respectively), there was no statistically significant difference between lung functions of the two groups at the end of followup. The persistence of respiratory symptoms was significantly predicted by initial FEF25%-75% and sensitivity to allergens (P = 0.03 and P = 0.04, respectively). Conclusions: We concluded that the risk factors for the persistence of respiratory symptoms in our patient population have been low FEF25%-75% value and sensitivity to allergens at referral.
Keywords: LONG-TERM TREATMENT; NATURAL-HISTORY; INHALED CORTICOSTEROIDS; PROGNOSTIC FACTORS; PULMONARY-FUNCTION; CHILDREN; RESPONSIVENESS